HEART- HEALTHY NATURAL INGREDIENTS FOR CHOLESTEROL REDUCTION - Chatterjee, Bandana; Modi, Kanchan; Patel, Tinkal (International Journal of Clinical and Biomedical Research, 2015)
Now-a-days people are shifting towards western lifestyle and food which is increasing the level of cholesterol and hence increase in risk of cardiovascular diseases. Cardiovascular disease is causing premature death at the highest rate than any other disease. In market various cholesterol reducing drugs are present which people are consuming. Intake of these drugs causes various life threatening side effects. People can switch to natural sources of reducing cholesterol level which will be healthy as well as safe. Plant sterol, plant stanol and plant stanol ester are safe as they are from a plant source and is proven to lower cholesterol level. Foods enriched in these components should be consumed to reduce the risk of cardiovascular disease. There are several cholesterol reducing ingredients which is still not known among the mass. Dietary fibers, all type of nuts, garlic, apple, soy products, green tea are some of the many natural cholesterol reducing ingredients which is discussed in this review. Various studies have been conducted to show that these ingredients do reduce the cholesterol level in a noticeable way. FDA has also approved various health claims regarding these ingredients. KEYWORDS: Cardiovascular disease; Cholesterol; Plant sterols; Natural cholesterol reducing ingredients.